ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI STATUS GIZI BALITA DI KOTA SURAKARTA - Kusumawati, Dewi; Ma’rifah, Bahriyatul; Rose, Sophia; Avianty, Selma (Universitas Pahlawan Tuanku Tambusai, 2024)
Toddlers are one of the groups prone to experiencing nutritional problems such as macronutrient deficiencies, excess macronutrients and micronutrient deficiencies. Differences in the area of residence, socioeconomic and lifestyle of the population can create a risk of malnutrition in children. The causes of nutritional status problems are divided into basic causes, indirect causes and direct causes. The aim of this research is to analyze the factors that influence the nutritional status of toddlers in the city of Surakarta. This research is an observational study with a cross sectional design. The research subjects were selected by purposive sampling with 128 toddlers aged 12-59 months. Data on subject characteristics and mother's level of knowledge used a questionnaire. Data on nutritional status of toddlers was obtained from anthropometric measurements with H/A and W/H indicators. Food intake data was obtained using the Semi Quantitative Food Frequency Questionnaire (SQ FFQ) method. The results of this study were abnormal nutritional status according to H/A (short and very short) of 14.9%, abnormal nutritional status according to W/H (under and over nutrition) of 29.7%. Birth weight, protein intake and maternal age influence the nutritional status of toddlers according to H/A. Birth weight, energ<y and protein intake influence the nutritional status of toddlers according to W/H (p<0,05). Acute nutritional problems for toddlers in urban areas are influenced by birth weight, energy and protein intake. Chronic nutritional problems for toddlers in urban areas are influenced by birth weight, protein intake and maternal age. Keywords: acute, chronic, nutritional status, toddlers, urban